Določitev sončnega obsevanja urbanih območij s pomočjo odprtokodnega GIS modela - aplikacija na primeru Rožne doline v Ljubljani - Mangafić, Alen (Igra ustvarjalnosti, 2017)
The determination of solar irradiation is crucial when planning the installation of solar systems. There are different GIS models for determining solar irradiation, which differ from each other in terms of input data, hardware requirements, performance, reliability and suitability, depending on the specificity of the study area and the nature of the study. Because of their diversity, urban areas pose a greater challenge for the estimation of the potential of the received solar energy. In the article we present a methodology for determining the irradiation of roofs in urban areas using the GRASS GIS model r.sun, which executes the computation with high resolution spatial, atmospheric and meteorological data. The used input data is freely available for the entire territory of Slovenia. The proposed methodological approach was tested on the area of the town quarter Rožna dolina in Ljubljana city with the northern part of Vič. The area is very diverse according to the typology of the built objects, the land cover and altitude. differences.
Keywords: Copernicus; GIS; lidar; Molusce; r.sun; Slovenia; Slovenija; Solar irradiation; sončno obsevanje